Possible Impact from Foreign Bank Presence to the Performance of Local Commercial Banks in Vietnam - Pham, Quoc Viet; Nguyen, Minh Thy (International Journal of Economics and Financial Issues, 2020)
Research on the impact of the presence of foreign banks on the domestic banking industry in particular is a popular topic for policy implications. The paper examines whether the presence of foreign banks improves the performance of domestic commercial banks in Vietnam. On the sample of 26 domestic commercial banks and 9 fully foreign-owned banks in Vietnam in the period 2009-2018, the research result shows that the presence of foreign banks reduces the profitability of domestic commercial banks, whereas does not have any impact on their operating costs, showing that the combination of spillover effects and competition effects has not caused a positive impact on Vietnamese banking industry. This result leads to policy implications that competition and the introduction of substitute products should be promoted, in order to make good use of the benefits of the entry of foreign banks. Keywords: foreign bank presence, bank performance, spillover effect, competition effect. JEL Classifications: G21, G34 DOI: https://doi.org/10.32479/ijefi.9297